Effect of (S.A.Q) Exercises to Development the Maximum Anaerobic Capacity and Shooting Skill by Inside the Foot of Football For Youth - Tahseen Muhammad Farhan; Ahmed Murtda Abid Al Hussain; Hussein Mnaty Sachit (Indian Journal of Forensic Medicine & Toxicology, 2021)
The importance of the research lies in preparing exercises in a modern training method (S.A.Q) thatcontribute to development of the maximum anaerobic capacity affecting the performance of soccer scoringfor youth, as well as to identify the effect of these exercises to developing the maximum anaerobic capacityand scoring skill within the foot of football for youth. As for the research problem, through the researchers’experience, they found that most of the exercises are limited to the offensive physical side and their focusis largely on scoring football in general and not focusing on scoring within the foot in particular, as wellas not paying attention to the physiological aspect of the player during training and competition, whichreflected negatively on the performance of most of the players. The researchers have identified the researchcommunity and the deliberate method of the football players represented by Al-Hussein Sports Club at theage of (19 years), whose number is (23) players for the training season (2020-2021). The research samplewas chosen by (14) players and a percentage of (60.869)% of the community Searching, (6) players wereselected for the reconnaissance experiment and (3) goalkeeper players were excluded.